How heterogeneous beliefs trigger financial crises - Florian Schuster; Marco Wysietzki; Jonas Zdrzalek (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
We present a theoretical framework to characterize how financial market participants contribute to systemic risk, allowing us to derive optimal corrective policy interventions. To that end, we embed belief heterogeneity in a model of frictional financial markets. We document the asymmetry that, by their behavior, relatively more optimistic agents contribute more strongly to financial distress than more pessimistic agents do. We further show that financial distress is generally more likely in an economy whose agents hold heterogeneous rather than homogeneous beliefs. Based on these findings, we propose a system of non-linear Pigouvian taxes as the optimal corrective policy, which proves to generate considerable welfare gains over the linear policy advocated by former studies.
Keywords: D84; E44; G28; H23; 330; Financial amplification; pecuniary externalities; collateral constraint; financial crisis; belief heterogeneity; macroprudential policy